Persepsi Mahasiswa PGSD Terhadap Kesiapan Menghadapi Dunia Kerja Sebagai Pendidik - Lisa Jamiatu Safitri; Delfi Rahmadhani; Jesi Alexander Alim; Mitha Dwi Anggriani (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to describe the perceptions of PGSD FKIP students at Riau University regarding their readiness to face the world of work as educators. The background of the research is based on the importance of mastering the four teacher competencies, namely pedagogic, professional, personality, and social, as stated in Law Number 14 of 2005 concerning Teachers and Lecturers. The research used a descriptive quantitative approach with a survey method. The research instrument was a Likert scale questionnaire consisting of 20 statement items. The research subjects were PGSD students of FKIP Riau University, with a total of 35 respondents. The data were analyzed using descriptive statistical techniques through the calculation of frequency, percentage, average, and total score, then categorized based on certain assessment criteria. The results showed that student readiness was generally in the good category, with highest achievement in the personality aspect (87.1%, very good category), while the pedagogical (73.24%), professional (75.85%), and social (78.2%) aspects were in the good category. These findings indicate that student teachers have positive attitudes and characters to become professional educators, but it’s still necessary to strengthen the mastery of pedagogical and practical skills to be more optimal in facing the world of work.